An Environmental Assessment for Municipal Organic Waste and Sludge Treated by Hydrothermal Carbonization - Diaz-Robles, L; Espinoza-Perez, A; Vallejo-Gallardo, F; Espinoza-Perez, L (Elsevier B.V., 2022)
Climate change is the world s greatest challenge today, the reason why it is urgent to optimize industrial processes and find new renewable energy sources. Hydrothermal carbonization (HTC) is one of the Waste-to-Energy technologies with greater projections due to its operative advantages. However, for its large-scale implementation, there are challenges related to the variability of the composition of the waste biomass and the seasonal and geographical availability. This research applied the Life Cycle Analysis methodology to evaluate the environmental impacts caused by three biomasses blends as raw material in the HTC process at laboratory scale. The blends analyzed considered different organic fractions of municipal solid waste (food and pruning) and sewage sludge. The results showed that blend 1 had a lower environmental impact for the case of production in the experimental laboratory level, compared with blends 2 and 3. This is mainly due to its greater calorific value and mass yield, which allows obtaining more hydrochar compared with the other blends, increasing the energy efficiency of the process. Also, between 87.94% and 98.00% of the energy reduction is required to obtain neutral impacts regarding the energy requirements in the experimental laboratory level scenario and the Chilean energy matrix. The processing of blends in HTC has excellent potential in a context where municipal solid wastes have been disposed in sanitary landfills or dumps, as in most emerging countries. Since this study incorporated data from the literature, future studies should perform an elemental analysis to provide experimental and differentiated data. © 2022 Elsevier B.V.